μSR study of the nitronyl nitroxide p-CNPNN - Blundell, S; Pattenden, P; Chow, K; Pratt, F; Sugano, T; Hayes, W (1997)
We present the results of a muon-spin rotation/relaxation (μSR) study in zero and longitudinal magnetic fields and temperatures down to 40 mK of para-cyanophenyl nitronyl nitroxide (p-CNPNN). This layered material is expected to show ferromagnetic interactions on the basis of susceptibility measurements. In a zero-field μSR experiment, the spins of muons which are implanted in diamagnetic states will precess in any local internal fields. Hence a study of precession frequencies and/or relaxation rates can be used to follow the magnetic order parameter as a function of temperature. We find strongly temperature dependent muon relaxation below ∼0.17 K similar to that found recently in 1-NAPNN, indicating a magnetic transition at this temperature.